First year nursing students’ reflections about developing their verbal nursing skills during their nursing education in China: a qualitative study - Zhu, Xiaoling; Rask, Mikael; Xu, Hongbo (Frontiers in Public Health, 2023)
Objective: To explore the expectations of the students about developing their verbal interaction skills during nursing education. Background: Nursing students’ communication skills were not fully developed in China. Students have many challenges to face regarding developing their nursing skills, especially interaction skills, when they start their education. Design: A qualitative design was used in this research. Method: Twelve second-semester undergraduate nursing students were interviewed on the basis of purposive sampling, and qualitative content analysis was employed. Results: The main theme was ‘to intertwine caring interactional skills with knowledge’ and consisted of two sub-themes: ‘facilitating a caring nurse-patient relationship’ and ‘using a knowledge base for performing nursing care’. The first sub-theme comprises two categories, ‘caring approach’ and ‘helping and involving the patient in care’, with three and two subcategories, respectively. The second sub-theme comprises the two categories, ‘knowledge needed to be able to understand the patient’ and ‘health and treatment information’, with three and two subcategories, respectively. Conclusion: A synthesis of both knowledge and practise is needed to improve the nursing students’ interaction and professional skills during their nursing education.